Textual construction of the hearing-impaired students’ recount texts: A case of students with special needs in writing to mean - Gunawan, Wawan; Wirza, Yanty; Holik, Nici Azhari (Indonesian Journal of Applied Linguistics, 2020)
Being cohesive in writing for the hearing-impaired students is very crucial, serving as an alternative means of expressing ideas without using sign language in communicating with people in general. This study aims to analyze the textual structure of the hearing-impaired students’ recount texts to instantiate how they structure language in communication. This study focused on investigating the choice of theme and thematic progression patterns as an instantiation of making meanings among the hearing-impaired students as a minority group of students with special needs. The data were 36 recount texts of high and low achiever students collected from three educational levels: elementary, junior high, and senior high schools. Following a qualitative approach to data collection and analysis, this study relied on Systemic Functional Linguistics as the main conceptual framework for investigating types of theme and thematic progression patterns, and how these two elements showed the features of writing to mean among the hearing-impaired students. In terms of theme choices, the findings indicate that low achiever hearing-impaired students employed more marked themes with a lack of ability in writing to mean. In terms of thematic progression, theme reiteration pattern was the most frequently employed pattern, indicating a strong intention to the topic. The study informs that the textual description of the hearing-impaired students’ writings could help the teachers understand what and how to teach to improve their writing to mean.